Confined space design by nanoparticle self-assembly. Issue 5 (11th January 2021) - Dichiarante, Valentina; Pigliacelli, Claudia; Metrangolo, Pierangelo; Baldelli Bombelli, Francesca
Abstract : This perspective gives an outlook on the design of interparticle confined nanocavities in self-assembled NP systems and their functional relevance. Abstract : Nanoparticle (NP) self-assembly has led to the fabrication of an array of functional nanoscale systems, having diverse architectures and functionalities. In this perspective, we discuss the design and application of NP suprastructures (SPs) characterized by nanoconfined compartments in their self-assembled framework, providing an overview about SP synthetic strategies reported to date and the role of their confined nanocavities in applications in several high-end fields. We also set to give our contribution towards the formation of more advanced nanocompartmentalized SPs able to work in dynamic manners, discussing the opportunities of further advances in NP self-assembly and SP research.